The Technique of Directing the Sex of Betta Fish (Betta Sp.) Larval Stage (H3, H5, and H7) using Coconut Water (Cocos Nucifera) - Rohayati, Cucu; Utomo, Deny Sapto Chondro; Adiputra, Yudha Trinoegraha (Jurnal Perikanan dan Kelautan, 2021)
Betta (Betta sp.) is an anabantidae fish with sexual development that can be directed at the embryonic and larval stages. One way to direct the sex development of these fish is by using hormone therapy using natural ingredients. Coconut water is one of the natural ingredients that can be used because it contains high potassium. This potassium can convert cholesterol in fish body tissue to pregnenolone which will affect the increase in testosterone production. This study aims to determine the best dose and age group in directing the sex of Betta fish experimentally using a randomized block design (RBD) with 4 treatments and 3 replications. The immersion treatment of larvae in the age group of 3 days, 5 days, and 7 days for 15 hours with a dose of 0%, 10%, 20%, and 30% coconut water was carried out in a 3 L jar containing 30 larvae. The results showed that coconut water was able to influence the increase in the percentage of male betta fish (P <0.05) with the highest value at a dose of 30% as much as 86.26 ± 8.34% and the 3 day larvae age group of 72.78 ± 16.03, and have a different effect on other treatments. In addition, the survival calculated after immersion shows a value of 100%, meaning that coconut water does not have a harmful effect on fish. Based on the results of this study, the best treatment for directing the sex of betta fish is a dose of 30% coconut water with the 3 day age group.